EFFECTIVENESS OF MINDFULNESS-BASED INTERVENTIONS FOR REDUCING STRESS AMONG NURSES: A QUALITATIVE STUDY AT KHYBER TEACHING HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Stress among nurses is an escalating problem given its impact on their mental health and the quality of care offered to patients. Mindfulness-based Interventions have received praise as MBIs for effective stress relief, although there is little qualitative research in Pakistani healthcare systems. This study looks into the impact of MBIs on stress relief for nurses at Khyber Teaching Hospital. A qualitative exploratory design was used, which consisted of 25 nurses that were purposefully sampled for semi- structured interviews. Data were collected through open-ended questions regarding stress and perceptions of MBIs and barriers to implementation. Patterns and themes were identified using the thematic analysis approach and NVivo software. The major findings indicated that the nurses operate under a lot of stress because of their workload, emotional exhaustion, and inadequate resources. Participants regarded MBIs as efficacious in stress management because it enabled them to better manage their emotions and direct their attention to the required tasks. Nonetheless, some barriers like limited time and inadequate training prevented proper application. Some facilitators included organizational backing and encouragement from colleagues. The need for institutional and more informative support is emphasized in the study in accordance with the ability of MBIs to help relieve stress among nurses. These findings enhance the developing literature on MBIs and healthcare, especially regarding Pakistani context. The findings could be validated better if future research included larger sample sizes with a wider demographic and utilized mixed-methods techniques.